14-YEAR-OLD MALE WITH SELECTIVE MUTISM – CASE REPORT - Sidarta, Nuryani; Nathania, C. (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Trisakti, 2024)
Selective mutism is a rare anxiety disorder characterized by an individual's persistent inability to speak in particular social environments, such as at school or in public places, while being able to communicate effectively and comfortably in other environments, like at home or with close family and friends. 1 Selective mutism commonly manifests during early childhood, affecting approximately 0.2% to 0.8% of children, with a higher prevalence observed in preschool environments.2 This disorder can profoundly disrupt a child's developmental trajectory, potentially leading to significant social and academic impairments if not addressed promptly.3. T his case report explores the developmental and communication challenges faced by a 14-year-old teenage boy presenting with significant delays in social communication skills. Referred to a developmental facility due to concerns about his social interaction and communication abilities. Patient’s symptoms and behaviors align with a diagnosis of Selective Mutism as defined by the DSM-V criteria This study provides a detailed account of how parents facing difficulty in obtaining an accurate diagnosis, which ultimately impacts the appropriate management and treatment. Limitations in speaking in public are often interpreted as part of a child's shy and quiet personality. As a result, this can lead to delays in diagnosis and eventually affect his language skills. Good awareness from parents and professionals is needed for early detection. As a professional, the ability to make an accurate diagnosis is essential to provide appropriate interventions for better prognosis and prevent further complications.